The Effect Of Adding Pumpkin Puree On Organoleptic Properties, Nutrients Content And Economic Value Of Dumbeg As An Alternative Snack High In Vitamin A - widowati, nadia cahya (Jurnal Gizi dan Kesehatan Nusantara, 2024)
The trend in food choices in today’s society is not only to prioritize taste but also to consider nutritional aspects and their role in develop body health. Indonesia has many cases of health problems regarding nutrition, including vitamin A deficiency. Technology is now very developed, giving rise to many innovations and creativity in food products that use pumpkin puree and other ingredients. Dumbeg is a traditional snack that is usually consumed during earth charity events in various regions. Dumbeg can be modified by adding pumpkin puree as an alternative snack high in vitamin A. This research aims to determine the organoleptic properties, nutritional content in the form of beta carotene and the economic value of adding yellow pumpkin puree to dumbeg. This research method uses an experimental method with the addition of 3 different pumpkin puree formulas. The independent variable of this research is the addition of pumpkin puree while the dependent variable is organoleptic properties, nutritional content of beta carotene and economic value. The data collection technique used a hedonic test with 5 trained panelists and 40 semi-trained panelists. The results of the research showed that the addition of pumpkin puree to dumbeg could influence the color, taste, texture and overall parameters of the dumbeg with p<0.005 and had no effect on the aroma with p>0.005. The best dumbeg results were obtained by adding 125 g of yellow pumpkin puree with the nutritional value of beta carotene being 3.43 mg/g. This amount is able to meet the need for snacks high in vitamin A and has an economic value that can be compared with market prices.